Book Review: Transforming HR: Creating Value Through People. (23rd June 2006) - Nolan, John
Reddington, M., Williamson, M., Withers, M. (2005). Transforming HR: Creating Value Through People. Oxford, Elsevier Butterworth-Heinemann. ISBN 0-7506-6447-9